A new partnership framework for education with geoparks at its core: a proposal through the evaluation of the school education program in Shikaoi, Japan - Xiang, Shirou; Watanabe, Teiji (Geotourism/Geoturystyka, 2025)
The primary objectives of geoparks are to conserve geoheritage, enhance public awareness and understanding of geoscience, and drive sustainable economic growth in local communities. Education acts as the cornerstone in achieving these three objectives, as it provides the necessary foundation for their realization. This study proposes a new educational framework to promote the sustainable development of geoparks by evaluating the effecacy of the past geoeducation program. Specifically, this study focused on the Tokachi-Shikaoi Geopark and Hokkaido Shikaoi High School. A mixed methodology was employed, including content analysis of the textbooks, online questionnaire surveys of high school students, and field interviews with key informants. The results revealed that while geoeducation with well-prepared textbooks was encouraged in schools in Shikaoi Town until 2018, there is a need to revitalize geopark education in an alternative way for the future. We proposed a new partnership framework for the educational program among the  geopark, universities, elementary, junior high, and high schools, and other stakeholders to maximize the geopark resources in the proposed program through the effective use of existing textbook assets. The results of the questionnaire surveys found that not only indoor learning with textbooks, but also outdoor learning at geosites is important. The results of the interview survey suggested the need to offer training and support for schoolteachers. To address budget constraints, this study proposed the inclusion of support from universities and the introduction of e-textbooks featuring geopark-related knowledge. This study highlights the crucial role of education in promoting sustainable development in Tokachi-Shikaoi Geopark. The insights gained have broader implications for education in other geoparks, offering valuable guidance for enhancing the quality and effectiveness of education in geoparks.